2017
DOI: 10.1007/s12010-017-2462-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chitosan-Based Films Containing Gelatin, Chondroitin 4-Sulfate and ZnO for Wound Healing

Abstract: In this work, chitosan-based films containing gelatin and chondroitin-4-sulfate (C4S) with and without ZnO particles were produced and tested in vitro to investigate their potential wound healing properties. Chitosans were produced from shrimp-head processing waste by alkaline deacetylation of chitin to obtain chitosans differing in molecular weight and degree of deacetylation (80 ± 0.5%). The film-forming solutions (chitosan, C4S and gelatin) and ZnO suspension showed no toxicity towards fibroblasts or kerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 39 publications
3
15
2
1
Order By: Relevance
“…In our study, no postoperative adverse effects such as infection, pyogenesis, and body fluid effusion occurred in any animals throughout the experimental period. More importantly, it is worth noting that the FTWS of 900 mm 2 reported here is higher than in previous studies on chitosan showing re-epithelialization at 14 days, with an FTWS ranging from 20 mm 2 to 150 mm 2 [38,[43][44][45][46]. In all cases, the wound sites were significantly lower than the case reported here.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In our study, no postoperative adverse effects such as infection, pyogenesis, and body fluid effusion occurred in any animals throughout the experimental period. More importantly, it is worth noting that the FTWS of 900 mm 2 reported here is higher than in previous studies on chitosan showing re-epithelialization at 14 days, with an FTWS ranging from 20 mm 2 to 150 mm 2 [38,[43][44][45][46]. In all cases, the wound sites were significantly lower than the case reported here.…”
Section: Discussioncontrasting
confidence: 73%
“…Immunohistochemistry demonstrated that keratin 10 (CK10) was uniformly expressed in the epithelium of the CP1000 group, whereas it was mostly expressed in the basal and suprabasal layers of CPR and CP500 groups, like normal skin. The wound contraction observed 14 days after implantation seemed to be very high for all types of patches, especially CPR and CP500, considering that the initial scar dimensions were higher than those presented in many other studies [44,45,47].…”
Section: Discussionmentioning
confidence: 54%
“…The wound healing capacity of the system was evaluated in rat models with full-thickness excision. After six days, results showed a significant decrease (14–35% more) of the wound compared with that obtained in control ones [ 129 ]. Selected ZnO based nanoplatforms for wound healing are summarized in Table 6 .…”
Section: Zno Nanoplatforms For Wound Healingmentioning
confidence: 99%
“…Hair follicles, which have a major role in epithelial regeneration and wound healing, can also be considered as a reservoir for the penetration of NPs inside the skin [23]. The secretion of serum proteins and cells pronounced the formation of more exuberant crusts and resulted in more efficient healing of the wounds treated with ZnO, ZnO/Ext, ZnO/CuO/Ext and particularly ZnO/Ag/Ext [31]. Moreover, the deposition of collagen in wounds was investigated by Masson's trichrome staining.…”
Section: Resultsmentioning
confidence: 99%